2010
DOI: 10.1136/adc.2009.179564
|View full text |Cite
|
Sign up to set email alerts
|

Variations in breastfeeding rates for very preterm infants between regions and neonatal units in Europe: results from the MOSAIC cohort

Abstract: It is possible to achieve high breastfeeding rates for very preterm infants, but rates varied widely across regions and neonatal units throughout Europe.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
100
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(105 citation statements)
references
References 10 publications
3
100
0
2
Order By: Relevance
“…Lower breast feeding rates in the NICU compared to the postnatal wards in maternity hospitals has been previously reported (Wallace et al, 2013). Previous studies investigating breast feeding rates in NICU have primarily focused on a specific neonatal population (Bonet et al, 2010;Maia et al, 2011;Lee et al, 2012) and not on a population-based cohort. We have found that admission to the NICU, independent of the reason, including preterm childbirth and low birth weight, negatively impact on breast feeding.…”
Section: Discussionmentioning
confidence: 93%
“…Lower breast feeding rates in the NICU compared to the postnatal wards in maternity hospitals has been previously reported (Wallace et al, 2013). Previous studies investigating breast feeding rates in NICU have primarily focused on a specific neonatal population (Bonet et al, 2010;Maia et al, 2011;Lee et al, 2012) and not on a population-based cohort. We have found that admission to the NICU, independent of the reason, including preterm childbirth and low birth weight, negatively impact on breast feeding.…”
Section: Discussionmentioning
confidence: 93%
“…Units were purposely chosen to ensure geographical variability (Paris and suburbs), diverse sociocultural characteristics of the mothers (origin and social class), and variation of breastfeeding rates at discharge from the neonatal unit (high, medium, or low). 1 No unit refused to participate in the study. Interviewees were two lactation consultants, two nurses in charge of the pasteurization unit, two head nurses, two nurses, and one pediatrician.…”
mentioning
confidence: 97%
“…1 Variations in practices related to the management of breastmilk in European neonatal units may explain some of these differences. We sought to describe procedures for management of mother's own milk for infants born very preterm in the Ile-de-France region and to assess how these relate to existing French regulations and guidelines.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In this vulnerable population, MOM provides additional advantages, reducing the risk of necrotising enterocolitis and bronchopulmonary dysplasia (BPD), enhancing enteral tolerance, protecting against infections, and improving neuro-developmental and visual outcomes [2,3,4,5,6]. Regrettably, many barriers hinder breastfeeding in hospitalised neonates, resulting in lower breastfeeding rates and durations compared with healthy neonates [7]. There is therefore a critical need for further identification of interventions supporting breastfeeding in neonatal intensive care units (NICUs) [8,9].…”
Section: Introductionmentioning
confidence: 99%